Harmonizing the Administrative Court Legal System to Ensure Legal Certainty in the Administrative Lawsuit Time Limit: Harmonisasi Sistem Hukum Peradilan Tata Usaha Negara dalam Mewujudkan Kepastian Hukum Tenggang Waktu Gugatan - Kartabrata, Fajar Ramadhan; Ernawan, Moch Erick; Dwinanda, Irfan Alfieansyah (LITIGASI, 2025)
Individuals or private legal entities, as legal subjects, have the right to file a legal action against a beschikking or unilateral administrative decision, even when they are not explicitly named in such decision. Within the administrative court system, the time limit for filing a lawsuit serves as a formal mechanism to uphold the principle of legal certainty. However, the existing regulations particularly between the Administrative Court Law and the Government Administration Law remain inconsistent, resulting in legal uncertainty in the settlement of administrative disputes, especially for indirectly affected third parties. Using a statutory approach, this study analyzes the harmonization of Indonesia’s administrative court legal system to ensure legal certainty in determining the time limit for filing administrative lawsuits and proposes regulatory solutions through the formulation of a more coherent and implementable judicial regulation.